PERAN BUDAYA DALAM PEMEROLEHAN BAHASA ASING - Zelvia Liska Afriani (DISASTRA: PENDIDIKAN BAHASA DAN SASTRA INDONESIA, 2019)
This study aims at examining the role of culture in learning English as a foreign language. Previous researchers explained that there is an intimate relationship between language and culture. It is obviously mentioned that when someone is willing to learn a language, he also needs to learn its culture so as to master it fully. Therefore, the researcher would like to investigate whether the teachers at school has understood and implemented cultural literacy in the language classroom or not. In this study, the researcher used a descriptive qualitative study and gathered the information needed from some English teachers in North Bengkulu. The result shows that the English teachers has been aware of the importance of cultural literacy in English language classroom since it can enhance students’ communicative competence. There are some offered ideas that can be employed in introducing cultural literacy, such as using authentic materials, proverbs, role-play, students as cultural resources, ethnography study, and literature.